2014
DOI: 10.1002/jca.21370
|View full text |Cite
|
Sign up to set email alerts
|

Role of therapeutic apheresis in infectious and inflammatory diseases: Current knowledge and unanswered questions

Abstract: Apheresis can remove pathogens and mediators that contribute to pathogenic inflammatory responses in diseases not generally considered to be "Hematologic." Erythrocytapheresis can remove intracellular pathogens such as Babesiosis. Plasmapheresis can remove mediators of the inflammatory response in conditions such as sepsis, chronic autoimmune urticaria and malignant pertussis. Leukapheresis can remove potentially harmful leukocytes in Crohn's Disease and malignant pertussis. While apheresis can remove all of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Patients with a profound reduction of ADAMTS13 (defined by an activity < 30%) were compared to patients with less severe suppression of ADAMTS13 activity (≥ 30%) in terms of clinical parameters at the time of inclusion before TPE treatment. Patients with ADAMTS13 activity ≥ 30% showed a trend to less organ dysfunction as indicated by lower SOFA scores (16 (14-19) vs. 19 (17)(18)(19)(20)(21)(22), p = 0.095, Fig. 4a) and comparable severity of hemodynamic shock (NE dose, 0.884 (0.639-1.158) μg/ kg/min vs. 0.667 (0.516-1.273) μg/kg/min, p = 0.529, Fig.…”
Section: Adamts13 and Correlation With Clinical Parameters Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a profound reduction of ADAMTS13 (defined by an activity < 30%) were compared to patients with less severe suppression of ADAMTS13 activity (≥ 30%) in terms of clinical parameters at the time of inclusion before TPE treatment. Patients with ADAMTS13 activity ≥ 30% showed a trend to less organ dysfunction as indicated by lower SOFA scores (16 (14-19) vs. 19 (17)(18)(19)(20)(21)(22), p = 0.095, Fig. 4a) and comparable severity of hemodynamic shock (NE dose, 0.884 (0.639-1.158) μg/ kg/min vs. 0.667 (0.516-1.273) μg/kg/min, p = 0.529, Fig.…”
Section: Adamts13 and Correlation With Clinical Parameters Of Diseasementioning
confidence: 99%
“…Although uncontrolled, we observed rapid stabilization of hemodynamics, improvement of fluid balances, and reduction of key pro-inflammatory cytokines and permeability factors. We believe that these positive surrogate effects can be attributed to two important aspects: (1) removal of harmful circulating molecules and (2) replacement of protective plasma proteins consumed by the disease process [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to lysis of red blood cells, Babesia pathogenesis is thought to be caused by host response to infection . After acute infection with babesiosis, there are systemic elevations in cytokines and adhesion molecules including tumor necrosis factor‐alpha (TNF‐α), interferon‐gamma (IFN‐γ), interleukin‐2 (IL‐2), interleukin‐6 (IL‐6), Eselectin, intracellular adhesion molecule 1 (ICAM‐1), and vascular‐cell adhesion molecule 1 (VCAM‐1) . Although moderate production of these pro‐inflammatory cytokines can be protective, excessive production may lead to severe babesiosis .…”
Section: Pathogenesismentioning
confidence: 99%
“…This process of asexual reproduction is asynchronous without the massive hemolysis that results in paroxysmal fevers and rigors in malaria [15]. In addition to lysis of red blood cells, Babesia pathogenesis is thought to be caused by host response to infection [15][16][17]. After acute infection with babesiosis, there are systemic elevations in cytokines and adhesion molecules including tumor necrosis factoralpha (TNF-a), interferon-gamma (IFN-g), interleukin-2 (IL-2), interleukin-6 (IL-6), Eselectin, intracellular adhesion molecule 1 (ICAM-1), and vascular-cell adhesion molecule 1 (VCAM-1) [16,18].…”
Section: Pathogenesismentioning
confidence: 99%
“…Another literature search using "therapeutic apheresis" only, "donor apheresis" only, and "cellular therapy" only was also performed and the results showed a yearly median of 17 (range: 6-26), 6 (range: [3][4][5][6][7][8][9], and 168 (range: 68-274) articles in each field, respectively during the same time-period. Hence, in 2012, the National Heart, Lung, and Blood Institute (NHLBI) in collaboration with the American Society for Apheresis (ASFA) held a sympo-sium to address the need for apheresis research, as well as the barriers to achieving that goal [3][4][5][6]. They concluded that there is a need to establish consortia in apheresis to facilitate research, networking, and collaboration among researchers, especially junior investigators, as well as to promote funding for apheresis research [3].…”
Section: Introductionmentioning
confidence: 99%